INFLUENCE OF FADAMA NSE BEBE TELEVISION PROGRAMME ON SUSTAINABLE AGRICULTURAL DEVELOPMENT IN ONDO STATE (Journal of Innovative, Communication and Media Studies, 2026)
Sustainable agricultural development is crucial to Nigeria’s pursuit of food security, environmental stewardship, and rural economic transformation. Mass Media is believed to be one of the key drivers of this noble initiative particularly agricultural television programmes which have emerged as influential platforms for disseminating knowledge and encouraging the adoption of sustainable farming practices. This study investigated the influence of Fadama Nse Bebe, an agricultural television programme, on sustainable agricultural development among farmers in Ondo State, Nigeria. Anchored in the Development Media Theory, the study explores how media exposure influences awareness, knowledge dissemination, and behavioural change in agricultural practices. A survey research design was employed, using purposive and multi-stage sampling techniques to select 384 respondents across five Local Government Areas: Akure South, Akure North, Ifedore, Ondo East, and Ondo West. The study assessed farmers’ awareness, viewership, and exposure to Fadama Nse Bebe as well as their adoption of the practices promoted. Findings reveal a high level of awareness and regular viewership of the programme among respondents. Notably, a significant number of farmers reported applying the knowledge acquired from the programme to improve their farming methods, particularly in areas of sustainable land use and resource management. Statistical analysis indicated a strong, positive correlation between programme exposure and adoption of sustainable agricultural techniques. The study concludes that agricultural television programming constitutes a viable tool for promoting sustainable agriculture. It recommends consistent programme scheduling and improved funding mechanisms to enhance media advocacy as well as address irregularities in broadcast, thereby maximizing its developmental impact.